1978
DOI: 10.1002/aja.1001510103
|View full text |Cite
|
Sign up to set email alerts
|

A morphological study of the human prepubertal and pubertal larynx

Abstract: Measurements were made from ten Caucasian male and ten Caucasian female cadaveric larynges ranging in age from 9 to 18 years. The sample was divided into prepubertal and pubertal groups of each sex, respectively. Each specimen was dissected and measured according to a specified protocol so that data on linear and angular dimensions of the laryngeal cartilages and the weight of each cartilage were obtained. Results from this study highlighted differences in the developmental morphology of the circumpubertal lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
8

Year Published

1984
1984
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(80 citation statements)
references
References 1 publication
3
68
1
8
Order By: Relevance
“…The adult male larynx is approxi mately 50°/o larger than the adult female's in the anterior-posterior dimension [Negus. 1949;Kahane. 1978] (fig.…”
Section: Thread 7: Sexual Dimorphism Of the Vocal Anatomymentioning
confidence: 99%
“…The adult male larynx is approxi mately 50°/o larger than the adult female's in the anterior-posterior dimension [Negus. 1949;Kahane. 1978] (fig.…”
Section: Thread 7: Sexual Dimorphism Of the Vocal Anatomymentioning
confidence: 99%
“…Especially in men, the laryngeal dimensions are smaller before puberty than during puberty (Kahane 1978). X-ray investigations of Pu¨schel and Nowakowsky (1954) in 23 patients (aged 19-58 years) with androgen deficiency revealed that ossification of thyroid cartilage does not correspond to age.…”
Section: Introductionmentioning
confidence: 95%
“…This is because acoustic differences between juveniles and adults primarily result from the differences in sizes of sound-producing structures (Fitch and Hauser, 2002). In humans and many other mammals, the f0 is inversely related to mass and length of the oscillating portions of the vocal folds (Titze, 1994), and both mass and length increase together with the growth of the larynx (Kahane, 1978(Kahane, , 1982. In most mammalian species, the growth of these sound-producing structures is related to the growth of the body, which results in a steady descent of f0 with age (for instance, Briefer and McElligott, 2011;Efremova et al, 2011;Campbell et al, 2014).…”
Section: Introductionmentioning
confidence: 98%